Leishmania HASP and SHERP Genes Are Required for In Vivo Differentiation, Parasite Transmission and Virulence Attenuation in the Host - Doehl, Johannes S P; Sádlová, Jovana; Aslan, Hamide; Pružinová, Kateřina; Metangmo, Sonia; Votýpka, Jan; Kamhawi, Shaden; Volf, Petr; Smith, Deborah F (PLoS pathogens, 2017)
Differentiation of extracellular Leishmania promastigotes within their sand fly vector, termed metacyclogenesis, is considered to be essential for parasites to regain mammalian host infectivity. Metacyclogenesis is accompanied by changes in the local parasite environment, including secretion of complex glycoconjugates within the promastigote secretory gel and colonization and degradation of the sand fly stomodeal valve. Deletion of the stage-regulated HASP and SHERP genes on chromosome 23 of Leishmania major is known to stall metacyclogenesis in the sand fly but not in in vitro culture. Here, parasite mutants deficient in specific genes within the HASP/SHERP chromosomal region have been used to investigate their role in metacyclogenesis, parasite transmission and establishment of infection. Metacyclogenesis was stalled in HASP/SHERP mutants in vivo and, although still capable of osmotaxis, these mutants failed to secrete promastigote secretory gel, correlating with a lack of parasite accumulation in the thoracic midgut and failure to colonise the stomodeal valve. These defects prevented parasite transmission to a new mammalian host. Sand fly midgut homogenates modulated parasite behaviour in vitro, suggesting a role for molecular interactions between parasite and vector in Leishmania development within the sand fly. For the first time, stage-regulated expression of the small HASPA proteins in Leishmania (Leishmania) has been demonstrated: HASPA2 is expressed only in extracellular promastigotes and HASPA1 only in intracellular amastigotes. Despite its lack of expression in amastigotes, replacement of HASPA2 into the null locus background delays onset of pathology in BALB/c mice. This HASPA2-dependent effect is reversed by HASPA1 gene addition, suggesting that the HASPAs may have a role in host immunomodulation.
Keywords: Disease Models, Animal; modely nemocí na zvířatech; myši; fluorescenční protilátková technika; myši inbrední BALB C; Insect Vectors; protozoální proteiny; Fluorescent Antibody Technique; Host-Parasite Interactions; Virulence; Immunoblotting; Mice, Inbred BALB C; interakce hostitele a parazita; Mice; Psychodidae; Animals; Protozoan Proteins; Antigens, Protozoan; hmyz - vektory; Cell Differentiation; zvířata; virulence; polymerázová řetězová reakce; antigeny protozoální; Leishmaniasis; leishmanióza; buněčná diferenciace; Polymerase Chain Reaction; imunoblotting; Leishmania major